Assessment of Postoperative Outcomes of Spine Fusion Patients With History of Cardiac Disease. Issue 8 (15th April 2022) - Ahmad, Waleed; Fernandez, Laviel; Bell, Joshua; Krol, Oscar; Kummer, Nicholas; Passfall, Lara; Naessig, Sara; Pierce, Katherine; Tretiakov, Peter; Moattari, Kevin; Joujon-Roche, Rachel; Williamson, Tyler K.; et al.
Abstract : Introduction: There is paucity on the effect of different cardiac diagnoses on outcomes in elective spine fusion patients. Methods: Patients undergoing elective spine fusion surgery were isolated in the PearlDiver database. Patients were stratified by having a previous history of coronary artery disease (CAD), congestive heart failure (CHF), valve disorder (valve), dysrhythmia, and no heart disease (control). Means comparison tests (chi-squared and independent samples t -tests, as appropriate) compared differences in demographics, diagnoses, comorbidities, procedural characteristics, length of stay, complication outcomes, and total hospital charges among the cohort. Results: In total, 537, 252 elective spine fusion patients were stratified into five groups: CAD, CHF, valve, dysrhythmia, and control. Among the cohort, patients with CHF had significantly higher rates of morbid obesity, peripheral vascular disease, and chronic kidney disease ( P < 0.001 for all). Patients with CAD had significantly higher rates of chronic obstructive pulmonary disease, diabetes, hypertension, and hyperlipidemia (all P < 0.001). Comparing postoperative outcomes for CAD and control subjects, CAD was associated with higher odds of myocardial infarction (odds ratio [OR]: 1.64 [1.27 to 2.11]) ( P < 0.05). Assessing postoperative outcomes for CHF versus control subjects, patients with CHF had higher rates of pneumonia, cerebrovascular accident (CVA), myocardial infarction, sepsis, and death ( P < 0.001). Compared with control subjects, CHF was a significant predictor of death in spine fusion patients (OR: 2.0 [1.1 to 3.5], P = 0.022). Patients with valve disorder compared with control displayed significantly higher rates of 30-day readmission ( P < 0.05) and 1.38× greater odds of CVA by 90 days postoperatively (OR: 1.4 [1.1 to 1.7], P = 0.007). Patients with dysrhythmia were associated with significantly higher odds of CVA (OR: 1.8 [1.4 to 2.3], P < 0.001) by 30 days postoperatively. Conclusion: Heart disease presents an additional challenge to spine fusion patients who are undergoing a challenging and risky procedure. Before surgical intervention, a proper understanding of cardiac diagnoses could give insight into the potential risks for each patient based on their heart condition and preventive measures showing benefit in minimizing perioperative complications after elective spine fusion.